Novel polymorphisms within the Dlk1-Dio3 imprinted locus in rat: a putative genetic basis for strain-specific allelic gene expression - Sittig, Laura J.; Redei, Eva E. (Frontiers in Genetics, 2012)
The imprinted iodothyronine deiodinase-III (Dio3) thyroid hormone metabolizing gene exhibits paternal expression in most fetal tissues, yet exhibits aberrant, maternal expression in the hippocampus in F1 offspring of Sprague Dawley (SD) x Brown Norway (BN) rats. The maternal hippocampal expression is associated with lower Dio3 mRNA levels specifically in the hippocampus. Here, we tested the hypothesis that genetic polymorphisms between the SD and BN parent strains cause this aberrant allelic Dio3 expression and contribute to behavioral sequelae of higher thyroid hormone levels locally in the hippocampus, including anxiety-related behavior. We mapped and sequenced the Dio3 gene and several previously unmapped regions in the Dlk1-Dio3 locus that could regulate imprinting of the Dio3 gene. In the Dio3 promoter we identified four novel polymorphisms between the BN and SD strains. Next we took advantage of the fact that the Long Evans (LE) strain exhibits identical polymorphisms as the SD strain in the region 5’ and including the Dio3 gene. By reciprocally crossing LE and BN strains we tested the relationship among Dio3 promoter region polymorphisms and Dio3 mRNA expression in the hippocampus. Aberrant strain-specific hippocampal Dio3 allelic expression replicated in the LE-BN reciprocal crosses, suggesting that hippocampal-specific imprinting of the Dio3 gene is not the result of a unique genetic or epigenetic characteristic of the SD rat strain, or a unique epistatic interaction between SD and BN. To our knowledge no other studies have reported a genetic x epigenetic interaction of genetic origin in the brain.